1991
DOI: 10.1111/j.1600-0609.1991.tb01538.x
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of carbonyl iron: A randomized, double‐blind study

Abstract: 49 female blood donors with iron‐deficiency anemia were treated with equal doses of iron either as carbonyl iron or ferrous sulfate in a randomized, double‐blind fashion. The prevalence of side‐effects was similar in the two groups. Mean values for hemoglobin concentration, mean corpuscular volume, corrected reticulocyte count, platelet count, serum iron, total iron‐binding capacity, transferrin saturation or erythrocyte proto‐porphyrin did not differ significantly between the two groups throughout the study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…When carbonyl iron is consumed without a meal in pharmacologic (100 mg) doses, it is reported to have a relative bioavailability in humans of about 70% that of ferrous sulfate. 43 It seems probable that the low levels of elemental iron (40 mg/kg) added to wheat flour would have little impact on iron nutrition, but the much higher levels added to commercial infant cereals (200-550 mgkg) together with vitamin C could contribute substantially to the prevention of iron deficiency anemia.…”
Section: Compounds Poorly Soluble In Dilute Acidsmentioning
confidence: 99%
“…When carbonyl iron is consumed without a meal in pharmacologic (100 mg) doses, it is reported to have a relative bioavailability in humans of about 70% that of ferrous sulfate. 43 It seems probable that the low levels of elemental iron (40 mg/kg) added to wheat flour would have little impact on iron nutrition, but the much higher levels added to commercial infant cereals (200-550 mgkg) together with vitamin C could contribute substantially to the prevention of iron deficiency anemia.…”
Section: Compounds Poorly Soluble In Dilute Acidsmentioning
confidence: 99%
“…If side-effects limit compliance, the medication can be administered with food, or the dose can be reduced. One 500-mg ferrous sulphate dose nightly at bedtime may be an effective therapy in adults [19]. …”
Section: Oral Iron Therapymentioning
confidence: 99%
“…treated rats revealed no morphological changes (data not shown). Devasthali et al (1991) reported that ferrous sulphate, as a dietary iron supplement, causes gastrointestinal side effects. Present findings indicate a significant decrease in body weight of iron-treated rats compared to controls.…”
Section: Figure 4 A: Western Blot For Brush Border Sucrase In Purifiedmentioning
confidence: 98%